Comparative Efficacy of Tamsulosin vs Tadalafil and Tamsulosin: In Treatment of Lower Urinary Tract Symptoms Secondary To Benign Prostatic Hypertrophy (BPH) - Sagun Bahadur Thapa Chhetri; Sudip Chaudhary; Manab Tiwari (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Benign prostatic hypertrophy (BPH) is common among aging men. Tamsulosin has long been used in medical management for troublesome Lower Urinary Tract Symptoms (LUTS). Tadalaﬁl has demonstrated effectiveness in addressing LUTS through several preclinical and clinical trials. We aim to assess the efﬁcacy of tamsulosin alone vs tadalaﬁl with tamsulosin given in symptomatic patients of BPH in a tertiary care teaching institution. MATERIAL AND METHODS This prospective observational longitudinal study was conducted at Universal College of Medical Sciences, Bhairahawa from October 2021 to March 2023. A total of 140 patients with BPH were divided into 2 groups; tamsulosin only (0.4mg once daily) and tamsulosin (0.4mg once daily) + Tadalaﬁl (5 mg once daily) group. IPSS, QoL (Quality of Life) were recorded on the ﬁrst visit and then at 2, 6 and 12 weeks. Similarly, voided urinary volume, Qmax (maximum ﬂow rate), PVR (post-voidal residual urine) were recorded at ﬁrst visit and then after 2 weeks. RESULTS There was a signiﬁcant improvement in the IPSS score, QoL, Qmax and PVR in both tamsulosin group and tamsulosin + tadalaﬁl group (p<0.001). The mean difference in improvement of IPSS score (10.8 vs 9.3), IPSS-QoL (2.73 vs 2.24), Qmax (4.9 vs 3.2) and PVR (36.87 vs 32.56) was more in tamsulosin + tadalaﬁl group compared to tamsulosin group. Similarly, mean difference in IPSS score in 2nd and 3rd visit is better in the combination group. CONCLUSION The combination of tamsulosin and tadalaﬁl was superior to tamsulosin alone in terms of IPSS, IPSS-QoL, Qmax and PVR.